Enhancing The Students’ Speaking Skill Through Peer and Self Assessment Method - Zam-zam Adam; Ali Halidin (Institut Agama Islam Negeri Parepare, 2020)
The purpose of this research was to find out the effectiveness of peer and self-assessment in enhancing students’ speaking skills at the second-grade students of SMA 3 Parepare. The subject of this research was the XI IPA 1 class which is consisted of 28 students. The sample was taken by using cluster sampling. The design of this research was pre-experimental with pre-test and post-test design. The researcher gave pre-test and post-test to know whether implementing peer and self-assessment methods can improve students’ speaking skills or not. The result of this research indicates that there was an improvement in the students’ speaking skills. It was shown in the students’ mean score of post-test (62.8) that was greater than the pre-test (19.5). Even, for the level significant (p) 5% and df = 27, and the value of the table is 1.703, while the value of the t-test is 1.825. It means that the t-test value is greater than the t-table (1.825 ≥ 1.703). Thus, it can be concluded that the students’ speaking skill is significant because previously the students’ speaking skill was low and after implementation peer and self-assessment methods there have been differences or development of speaking after getting the treatment. So, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted.